Battery pole piece, battery cell and lithium ion battery

By setting holes on the surface of the active material layer of the lithium-ion battery electrode sheet and filling the solid electrolyte, the problem of degradation of kinetic performance after increasing the electrode thickness is solved, and higher energy density and better low-temperature charging capacity are achieved.

CN222483401UActive Publication Date: 2025-02-14ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202421350157.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-14
Estimated Expiration
2034-06-13

AI Technical Summary

Technical Problem

While increasing the electrode thickness of the lithium-ion battery to increase the energy density, the kinetic performance decreases, especially after the electrolyte is consumed in the later stage of the cycle, an ion circuit breaker is easily formed, resulting in a decrease in the performance of the battery cell.

Method used

Several holes are provided on the surface of the active material layer of the battery electrode sheet, and solid electrolytes are filled in these holes to improve the circuit breaking problem of ion transmission channels and reduce the amount of electrolyte used.

Benefits of technology

By filling the solid electrolyte, the ion transmission channel of the battery pole is improved, the ion circuit breaking problem in the later stage of the cycle is avoided, and the dynamic performance and low-temperature charging capacity of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222483401U_ABST
    Figure CN222483401U_ABST
Patent Text Reader

Abstract

The utility model discloses a battery pole piece, a battery cell and a lithium ion battery, and relates to the technical field of battery pole pieces. The battery pole piece comprises a current collector and an active substance layer, and the active substance layer is coated on one surface or two surfaces of the current collector; wherein the surface of the active material layer is provided with a plurality of holes, and the plurality of holes are filled with solid electrolyte. According to the battery pole piece, the holes are filled with the solid electrolyte, and the solid electrolyte cannot be consumed in the later period of battery circulation, so that the problem of open circuit of an ion transmission channel of the battery pole piece is solved, and meanwhile, the use amount of the electrolyte can be reduced. In addition, since the solid electrolyte is used for filling, the ionic conductance of the lithium ion battery is slightly influenced by temperature, so that the charging capacity of the lithium ion battery at low temperature is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of battery pole pieces, and in particular to a battery pole piece, a battery core and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have been widely used in many fields due to their significant advantages such as high voltage, high specific energy, long life, environmental protection and safety, including but not limited to the mobile phones, digital cameras, laptops and power tools we use in daily life, as well as convenient small appliances, electric vehicles and energy storage systems.

[0003] With the rapid advancement of science and technology, the performance requirements for lithium-ion batteries have become increasingly stringent, among which energy density is particularly critical. Therefore, improving the energy density of lithium-ion batteries has become the research focus of the lithium battery industry at home and abroad.

[0004] In order to improve the energy density of lithium-ion batteries, a variety of methods are currently being explored and practiced, such as reducing the thickness of lithium-ion electrode current collectors and separators, and introducing silicon-based anodes with higher energy density. It is worth mentioning that increasing the thickness of lithium-ion battery electrodes is also an effective method. By increasing the thickness of the electrode, we can reduce the number of layers of battery cells inside the battery, thereby reducing the space occupied by the current collector and separator, thereby providing more space for active substances. In this way, more active substances can be carried per unit area of ​​electrode surface, thereby increasing the specific energy of lithium-ion batteries.

[0005] However, while thick electrodes increase the energy density of the battery cell, they also bring about the problem of decreased dynamic performance. At present, the industry often improves its dynamic performance by punching holes in the electrode. However, this method has a defect, that is, after the electrolyte of the punched electrode is consumed in the later stage of the cycle, an ion circuit will be formed, resulting in a decrease in battery cell performance. Therefore, how to maintain or even improve the dynamic performance while increasing the thickness of the electrode is still a problem that needs to be solved urgently. Utility Model Content

[0006] In view of the deficiencies in the prior art, the utility model provides a battery pole piece, a battery core and a lithium ion battery.

[0007] The utility model discloses a battery pole piece, comprising a current collector and an active material layer, wherein the active material layer is coated on one side or both sides of the current collector; wherein a plurality of holes are arranged on the surface of the active material layer, and solid electrolytes are filled in the plurality of holes.

[0008] According to an embodiment of the present invention, the diameter Φ of the hole is 0.05 to 0.2 mm, and the depth h of the hole is 15 to 35 um.

[0009] According to one embodiment of the present invention, the holes are distributed in a rectangular array.

[0010] According to one embodiment of the present invention, the hole spacing d between two adjacent holes is 0.5 to 2.5 mm.

[0011] According to one embodiment of the present invention, the filling ratio of the solid electrolyte is 90-100%.

[0012] According to one embodiment of the present invention, the calculation formula of the filling ratio is: p=V1÷V2, wherein V1 is the volume of the pores, and V2 is the filling volume of the solid electrolyte.

[0013] According to one embodiment of the present invention, the solid electrolyte is lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate (LLTO), lithium oxide (Li2O), lithium sulfide (Li2S), lithium aluminum titanium phosphate (LiAlPO4), lithium iron phosphate (LiFePO4) or polyethylene oxide (PEO).

[0014] According to one embodiment of the present invention, the battery pole piece is a negative pole piece.

[0015] The utility model discloses a battery core, comprising the battery pole piece as described above, and also comprising a positive pole piece and a separator. The positive pole piece, the separator and the battery pole piece are stacked in sequence and then wound to form a battery core.

[0016] The utility model discloses a lithium ion battery, comprising the above-mentioned battery core, wherein the battery core is packaged in a shell, and the shell is filled with electrolyte.

[0017] Compared with the prior art, the battery pole piece, battery cell and lithium ion battery of the utility model have the following advantages:

[0018] The battery pole piece of the utility model fills the hole with solid electrolyte, and the solid electrolyte will not be consumed in the later stage of battery cycle, thereby improving the circuit breaking problem of the ion transmission channel of the battery pole piece and reducing the amount of electrolyte used. In addition, since the solid electrolyte is used for filling, its ion conductivity is less affected by temperature, thereby improving the charging capacity of the lithium-ion battery at low temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0020] Figure 1 It is a schematic diagram of the structure of the battery electrode in the first embodiment;

[0021] Figure 2 It is a structural cross-sectional view of the battery electrode in Example 1.

[0022] Description of reference numerals:

[0023] 1. Current collector; 2. Active material layer; 3. Pores; 4. Solid electrolyte. DETAILED DESCRIPTION

[0024] The following will disclose multiple embodiments of the present invention with diagrams. For the purpose of clear description, many practical details will be described together in the following description. However, it should be understood that these practical details should not be used to limit the present invention. In other words, in some embodiments of the present invention, these practical details are not necessary. In addition, for the purpose of simplifying the diagram, some conventional structures and components will be depicted in a simple schematic manner in the diagram.

[0025] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present utility model.

[0026] Embodiment 1

[0027] This embodiment provides a battery electrode sheet, which is used to make a battery cell.

[0028] See also Figure 1 The battery pole piece includes a current collector 1 and an active material layer 2, and the active material layer 2 is coated on one side or both sides of the current collector 1. In this embodiment, the battery pole piece is a negative pole piece, and the active material layer 2 is coated on one side of the current collector 1, which is used as an example for description.

[0029] Specifically, a plurality of holes 3 are provided on the surface of the active material layer 2, and the holes 3 are formed by laser drilling. In the present embodiment, the shape of the hole 3 is cylindrical, the diameter of the hole 3 is 0.05-0.2 mm, and the depth of the hole 3 is 15-35 um. In addition, the holes 3 are distributed on the surface of the active material layer 2 in a rectangular array, and the spacing between two adjacent holes 3 is 0.5-2.5 mm. Preferably, the diameter of the hole 3 is 0.2 mm, the depth of the hole 3 is 20 um, and the spacing between two adjacent holes 3 is 2 mm.

[0030] Furthermore, the hole 3 is filled with a solid electrolyte 4. In this embodiment, the solid electrolyte 4 is selected from lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate (LLTO), lithium oxide (Li2O), lithium sulfide (Li2S), lithium aluminum titanium phosphate (LiAlPO4), lithium iron phosphate (LiFePO4) or polyethylene oxide (PEO).

[0031] Furthermore, the filling ratio of the solid electrolyte 4 is 90-100%, and the calculation formula of the filling ratio is: p = V1 ÷ V2, where V1 is the volume of the hole 3, and V2 is the filling volume of the solid electrolyte 4. Among them, the calculation formula of the volume of the hole 3 is: V1 = (m1-m2) ÷ ρ1, where m1 is the weight of the battery pole before punching, m2 is the weight of the battery pole after punching, and ρ1 is the density of the battery pole. The calculation formula of the filling volume is: V2 = (m3-m4) ÷ ρ2, where m3 is the weight of the battery pole after filling the solid electrolyte 4, m4 is the weight of the battery pole before filling the solid electrolyte 4, and ρ2 is the density of the solid electrolyte 4.

[0032] The battery pole piece is filled with solid electrolyte in the hole, and the solid electrolyte will not be consumed in the later stage of the battery cycle, thereby improving the circuit breaker problem of the ion transmission channel of the battery pole piece and reducing the amount of electrolyte used. In addition, since the solid electrolyte is used for filling, its ion conductivity is less affected by temperature, thereby improving the charging capacity of the lithium-ion battery at low temperatures.

[0033] Embodiment 2

[0034] This embodiment provides a battery cell for making a lithium-ion battery. The battery cell includes the battery pole piece described in the first embodiment, and also includes a positive pole piece and a separator. The positive pole piece, the separator and the battery pole piece are stacked in sequence and then wound to form a battery cell.

[0035] Embodiment 3

[0036] This embodiment provides a lithium ion battery, which includes the battery cell described in Embodiment 2. The battery cell is encapsulated in a shell, and the shell is filled with electrolyte.

[0037] In order to further illustrate the impact of the present invention on lithium-ion batteries, five battery electrode samples are provided below for detailed description.

[0038] Sample 1

[0039] The battery pole piece provided by sample 1 includes a current collector and an active material layer, and the active material layer is coated on one side of the current collector.

[0040] There are several holes on the surface of the active material layer, and the holes are distributed in a rectangular array. The hole is cylindrical, the hole diameter is 0.2mm, the hole depth is 20um, and the hole spacing between two adjacent holes is 2mm.

[0041] The hole is filled with a solid electrolyte, which is lithium aluminum titanium phosphate (LATP), and the filling ratio of the solid electrolyte is 80%.

[0042] Sample 2

[0043] Compared with sample one, the solid electrolyte filling ratio in the battery electrode provided by sample two is 90%.

[0044] Sample 3

[0045] Compared with sample one, the solid electrolyte filling ratio in the battery electrode provided by sample three is 100%.

[0046] Sample 4

[0047] Compared with sample one, the solid electrolyte filling ratio in the battery electrode provided by sample four is 110%.

[0048] Sample 5

[0049] Compared with sample one, in the battery electrode provided by sample five, the holes are not filled with solid electrolyte.

[0050] Sample 6

[0051] Compared with sample three, the solid electrolyte used in the battery electrode provided by sample six is ​​lithium lanthanum zirconium oxide (LLZO).

[0052] Sample 7

[0053] Compared with sample three, the solid electrolyte used in the battery electrode provided by sample seven is lithium lanthanum titanate (LLTO).

[0054] Sample 8

[0055] Compared with sample three, the solid electrolyte in the battery electrode provided by sample eight is lithium oxide (Li2O).

[0056] Sample nine

[0057] Compared with sample three, the diameter of the hole in the battery electrode provided by sample nine is 0.25 mm.

[0058] Sample 10

[0059] Compared with sample three, the diameter of the hole in the battery electrode provided by sample nine is 0.1 mm.

[0060] Sample 11

[0061] Compared with sample three, the diameter of the hole in the battery electrode provided by sample nine is 0.01 mm.

[0062] Sample 12

[0063] Compared with sample three, the diameter of the hole in the battery electrode provided by sample nine is 0.05 mm.

[0064] The battery electrodes of samples 1 to 5 were made into lithium-ion batteries using the same method, and were subjected to high temperature cycle test, low temperature cycle test and liquid retention test respectively. The test method is briefly described below:

[0065] High temperature cycle test: charge at 1.5C for 50 weeks at 45°C, fully charge after the cycle, disassemble in a low humidity room, and observe whether there are black spots on the negative electrode interface;

[0066] Low temperature cycle test: Charge at 0.15C for 50 weeks at -20℃, fully charge after the cycle, disassemble in a low humidity room, and observe whether there is lithium deposition on the negative electrode interface;

[0067] Liquid retention test: Lithium-ion batteries with a liquid retention gradient of 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, and 1.45 were cycled at room temperature for 1000 cycles to obtain the lowest liquid retention coefficient.

[0068] The above test results are as follows:

[0069]

[0070] By comparing samples 1 to 5, the difference lies in the different filling amounts of solid electrolyte. From the test results, we can see that:

[0071] Sample 1 was filled with too little solid electrolyte. In the high-temperature cycle test, after the electrolyte was consumed in the late cycle, ion circuits still occurred, and a small amount of black spots appeared. In the low-temperature cycle test, the concentration polarization near the pores increased due to the decrease in electrolyte ion conductivity, causing slight lithium precipitation at the interface. In the liquid retention test, when less electrolyte was injected, 1000 cycles could not be completed.

[0072] Since the filling amount of solid electrolyte is appropriate for Sample 2 and Sample 3, no black spots appear on the interface in the high-temperature cycle test, and no lithium precipitation appears on the interface in the low-temperature cycle test. In the liquid retention test, the liquid retention coefficient of 1.25 can still complete 1000 cycles;

[0073] Sample 4 was overfilled with solid electrolyte, which punctured the diaphragm and caused a short circuit, so all three tests could not be performed;

[0074] Since sample 5 was not filled with solid electrolyte, in the high-temperature cycle test, ion circuit still occurred after the electrolyte was consumed in the later stage of the cycle, and a large number of black spots appeared. In the low-temperature cycle test, due to the decrease in electrolyte ion conductivity, the concentration polarization near the pores increased, causing serious lithium precipitation on the interface. In the liquid retention test, the liquid retention coefficient below 1.35 did not complete 1000 cycles.

[0075] In addition, the battery electrodes of the above sample 3 and samples 6 to 8 were made into 1.35 liquid-retaining lithium-ion batteries using the same method, and high-temperature cycle tests were performed respectively. The test results are as follows:

[0076]

[0077] By comparing sample three with samples six to eight, the difference lies in the types of solid electrolytes. From the test results, it can be seen that the use of different solid electrolytes can improve the cycle capacity of lithium-ion batteries.

[0078] In addition, the battery electrodes of the above-mentioned samples 3 and 9 to 12 were respectively made into lithium-ion batteries using the same method, and were respectively tested for 100 cycles. The test results are as follows:

[0079]

[0080]

[0081] By comparing sample 3 with samples 9 to 12, the difference lies in the diameter of the hole. From the test results, we can see that the diameter of the hole should be 0.05-0.2mm. When the diameter of the hole is too large, it will lead to insufficient local CB value, causing lithium deposition around the hole. When the diameter of the hole is too small, it cannot be filled with solid electrolyte, causing lithium deposition around the hole.

[0082] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of the claims of the present invention.

Claims

1. A battery pole piece, characterized in that: The invention comprises a current collector (1) and an active material layer (2), wherein the active material layer (2) is coated on one side or both sides of the current collector (1); wherein a plurality of holes (3) are arranged on the surface of the active material layer (2), and a solid electrolyte (4) is filled in the plurality of holes (3).

2. The battery electrode according to claim 1, characterized in that: The diameter Φ of the hole (3) is 0.05 to 0.2 mm, and the depth h of the hole (3) is 15 to 35 um.

3. The battery pole piece according to claim 1, characterized in that: The holes (3) are distributed in a rectangular array.

4. The battery pole piece according to claim 3, characterized in that: The distance d between two adjacent holes (3) is 0.5 to 2.5 mm.

5. The battery pole piece according to claim 1, characterized in that: The filling ratio of the solid electrolyte (4) is 90-100%.

6. The battery pole piece according to claim 5, characterized in that: The calculation formula for the filling ratio is: p=V1÷V2, wherein V1 is the volume of the pore (3), and V2 is the filling volume of the solid electrolyte (4).

7. The battery pole piece according to claim 1, characterized in that: The solid electrolyte (4) is lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate (LLTO), lithium oxide (Li2O), lithium sulfide (Li2S), lithium aluminum titanium phosphate (LiAlPO4), lithium iron phosphate (LiFePO4) or polyethylene oxide (PEO).

8. The battery pole piece according to claim 1, characterized in that: The battery pole piece is a negative pole piece.

9. A battery cell, characterized in that: It comprises the battery pole piece as described in any one of claims 1 to 8, and also comprises a positive pole piece and a separator, wherein the positive pole piece, the separator and the battery pole piece are stacked in sequence and then wound to form the battery core.

10. A lithium ion battery, characterized in that: The battery cell comprises the battery cell according to claim 9, wherein the battery cell is encapsulated in a shell, and the shell is filled with electrolyte.

Citation Information

Cited By

  • Negative pole piece, preparation method thereof and all-solid-state battery

    CN122025548A